Natural Compounds as Prospective Corrosion Inhibitors for Iron: A DFT and Monte Carlo Study - Kareem, Rebaz Obaid; Azeez, Yousif Hussein; Omar, Karzan A.; Omer, Rebaz A.; Abdullah, Fuad O.; Mohammed, Haval H.; Hekim, Seda (Wiley-V C H Verlag Gmbh, 2025)
Corrosion poses significant environmental and economic challenges, necessitating the development of sustainable and effective inhibitors. This study aims to evaluate the anti-corrosion efficiency of sixteen natural flavonoid and polyphenolic compounds as potential eco-friendly inhibitors for iron. The compounds examined include dihydrocaffeic acid (1), rosmarinic acid (2), chlorogenic acid (3), apigenin 7-methyl ether (4), luteolin (5), apigenin (6), luteolin 7-methyl ether (7), luteolin 4-methyl ether (8), luteolin 3-methyl ether (9), luteolin 7,3'-dimethyl ether (10), tricetin 3',4',5'-trimethyl ether (11), luteolin 7,3',4'-trimethyl ether (12), tricetin 4'-methyl ether (13), tricetin 3,4'-dimethyl ether (14), delphinidin 3-O-glucoside (15), and cyanidin 3-glucoside (16). Density functional theory (DFT) calculations at the B3LYP/6-311+G(d,p) level were employed to analyze molecular reactivity and electronic properties, while Monte Carlo simulations were used to investigate the adsorption behavior of the compounds on the Fe (110) surface. The computational results revealed efficient electron charge transfer between the natural compounds and the iron surface, indicating strong adsorption and inhibition potential. Compounds 1-6 exhibited the most favorable interactions, whereas compounds 15 and 16 showed the lowest adsorption energies due to the presence of methoxy and hydroxy substituents. Overall, compounds 2, 15, and 16 emerged as the most promising green inhibitors, highlighting the potential of naturally derived molecules in corrosion protection applications.
Keywords: corrosion; DFT; flavonoids; metal surface; Monte Carlo simulations; natural compounds